Dokumen Penanganan Bongkar Muat Peti Kemas Pada PT.Temas Line Cabang Makassar - Purwantono, Tony (UKI Toraja Press, 2021)
This research aims to determine (1) the use of supporting documents needed in container loading and unloading activities, (2) what kind of handling documents needed in container loading dan unloading activities, and (3) types of loading and unloading equipment facilities used by PT Temas line cabang Makassar. The method used is quantitative method with qualitative data support. Data was collected by Library Research and Field Research like; direct observations techniques, in-depth interviews, and documentation. The data are presented by describing the primary and secondary data obtained during the research.The results showed that there are a lot of documents that must be prepared for loading and unloading activities, (1) such as documents before loading and unloading containers, (2) loading and unloading documents from ships to docks, documents to container stacking places, releasing goods from loading and unloading, and loading goods by direct transportation, (3) meanwhile the loading and unloading equipment facilities used , include forklifts, reach stackers, HMC, tronton, head trucks, chassis, and crane.